Upcycling of plastic waste into multi-walled carbon nanotubes as efficient organic dye adsorbent - Bogoeva-Gaceva, Gordana; Sokolovska, Meri; Stefov, Viktor; Najdoski, Metodija; Kovačič, Sebastijan (Slovenian Chemical Society, 2025)
Multi-walled CNTs with an average diameter of about 80 nm, a length of several micrometers and surface area (SBET) of 100 m2 g-1 were obtained by pyrolysis of low-density polyethylene waste. The potential of the resulting MWCNTs material to purify water containing organic dyes was tested with Bezaktiv Blau HE-RM (BB) and Bezaktiv Rot S-3B (BR) reactive dyes. 200 mg L-1 MWCNT material was used to follow the adsorption of 30 mg L-1, 40 mg L-1, 50 mg L-1 and 60 mg L-1 BB and BR at pH 3 and a temperature of ~25 oC. The results have shown that this material has a high potential as a sorbent, and its adsorption capacity of 257 mg g-1 (for Bezaktiv Blau HE-RM) and 213 mg g-1 (for Bezaktiv Rot) is close to some commercial MWCNTs and functionalized MWCNT-based adsorbents. The adsorption process was very fast, reaching 80-90 % of the dye removal in 10-15 minutes, and the equilibrium time was reached in 40-60 minutes. The adsorption isotherm showed that the Langmuir model was more suitable than the Freundlich model for describing the adsorption properties of the pollutants.